The role of human resources during a major product recall : TS Tech Alabama - Williams, Jaime; Gentry, Richard J. (London : SAGE Publications: SAGE Business Cases Originals, 2018)
The word "recall" strikes fear in the hearts of all business owners. Recalls not only tend to be a large expense for a company, but they also damage reputations, causing a dip in profits or even bankruptcy. Another serious, albeit less obvious, issue caused by recalls is the worry, stress, and uncertainty that all of the workers in the company will likely feel once a recall is announced. This case study looks at a major Honda recall due to defective parts made at TS Tech and the role of the Human Resources department before, during, and after the recall. Students are asked to focus specifically on the role Human Resources can play in employee retention during a recall.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Honda Giken Kogyo Kabushiki Kaisha; TS Tech Alabama; Product recall; Psychology, Industrial; Personnel management